2021
DOI: 10.1111/ejn.15397
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet prevents paclitaxel‐induced neuropathic nociception through activation of PPARγ signalling pathway and inhibition of neuroinflammation in rat dorsal root ganglion

Abstract: Chemotherapy‐induced peripheral neuropathy (CIPN) is a common side effect during the course of cancer treatment, which is mainly manifested as a series of sensory abnormalities. At present, there are no recommended prevention or treatment strategies, and the underlying mechanisms are unclear. The ketogenic diet (KD), a special diet that is high in fat and low in carbohydrate intake, shows good therapeutic potential in children with epilepsy. In this study, it was found that KD significantly prevented paclitaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Overall, these findings are consistent with emerging evidence that suggest a ketogenic diet may benefit MGO-driven painful pathologies. 13,17,31,32,44 These results suggest a broader application of ketogenic diets as therapeutic interventions in other MGO-related pathologies and chronic pain conditions.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Overall, these findings are consistent with emerging evidence that suggest a ketogenic diet may benefit MGO-driven painful pathologies. 13,17,31,32,44 These results suggest a broader application of ketogenic diets as therapeutic interventions in other MGO-related pathologies and chronic pain conditions.…”
Section: Discussionmentioning
confidence: 89%
“…[12][13][14]17,31,32 We and others have demonstrated success in using a ketogenic diet in reversing small-fiber neuropathies where MGO accumulation has been implicated, including DPN 12,13,17 and chemotherapy-induced neuropathy. 44 Moreover, Salom ón et al 33 demonstrated that MGO can be scavenged in blood by the ketone body acetoacetate.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies in ketolysis have been recently revealed in neurodegenerative diseases, including Friedreich’s ataxia and amyotrophic lateral sclerosis [14, 15]. Meanwhile, ketogenic diets are being studied in various neuropathies [17-19, 24, 25, 47, 48]. Our findings on the loss of Oxct1 and SCOT in peripheral neurons provide new information towards our understanding of ketone oxidation for developing and maintaining the peripheral sensory nervous system.…”
Section: Discussionmentioning
confidence: 82%
“…There is mounting evidence that ketone utilization is protective [17, 24, 25] and, in some cases, promotes regeneration [19] in the somatosensory nervous system of rodent models of chronic pain and neuropathy. SCOT is a mitochondrial enzyme expressed in peripheral tissues and required for ketolysis, catalyzing the conversion of acetoacetate and succinyl-CoA to acetoacetyl-CoA and succinate.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying PTX-induced neuropathic pain is complicated andrecent ndings suggested thatPTX-induced peripheral neuropathy is often associated with neuroin ammation in the peripheral nervous system [9][10][11]. For example, compared with control rats, it is found that plasma levels of IL-1α, IL-1β, IL-6, TNF-α, INF-γ and MCP-1 were signi cantly upregulated in PTX-treated rats [12].…”
Section: Introductionmentioning
confidence: 99%